COOPÉRATION COMMERCIALE OUGANDO-CONGOLAISE : Opportunités et des défis. - Justin Bahinduka Bessisa (IJRDO - Journal of Social Science and Humanities Research, 2019)
April 19, 2018, the Democratic Republic of Congo (DRC) and Uganda signed an agreement concerning commercial cooperation in the Ugandan city of Kasese. By this agreement, the two States committed to vary the exchanges of goods and services, to promote the investments in the sector of the factory and to eliminate the trade barriers. This agreement intervenes in a context where the two countries try to turn the page of the adversarial relations that they maintained during last decades. However, the present survey interrogates the opportunities of this bilateral agreement. Besides, an attentive exam is dedicated to the obstacles that reduce the efficiency of this cooperation and to the corrective measures capable to optimize the commercial cooperation between the two States.